2013
DOI: 10.1111/cch.12082
|View full text |Cite
|
Sign up to set email alerts
|

The importance of identity and empowerment to teenagers with developmental co‐ordination disorder

Abstract: The current work highlights the need for services to adopt a model of DCD where the young person talks about what they can do and considers strategies of overcoming their difficulties. This has implications for education and future intervention strategies that focus on fostering psychological resilience and educational coping strategies rather than simply attempting to improve motor skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 30 publications
(36 reference statements)
5
86
0
Order By: Relevance
“…Lingam et al (2013) used qualitative interviews to gain an in-depth understanding of the experiences and aspirations of a group of young people with disabilities. They found that, for these youth, identity formation is a combination of their life experiences and how they perceived their disability, including the ensuing differences and difficulties.…”
Section: Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lingam et al (2013) used qualitative interviews to gain an in-depth understanding of the experiences and aspirations of a group of young people with disabilities. They found that, for these youth, identity formation is a combination of their life experiences and how they perceived their disability, including the ensuing differences and difficulties.…”
Section: Identitymentioning
confidence: 99%
“…Furthermore, the adolescents' self-perception was specifically influenced by their perception of how friendship groups saw them in school and their perception of their family's attitude toward them at home. Finally, a positive sense of identity and self-worth stemmed from being part of a social network that provided a sense of belonging, preferably one that valued differences as well as similarities (Lingam et al 2013). …”
Section: Identitymentioning
confidence: 99%
“…Handwriting and executive functioning difficulties (e.g. organization and planning, prioritizing, problem solving and multi‐tasking) affected the ability of youth with DCD to perform academic activities adequately and in a timely manner (Kirby et al , , , ; Kirby ; Tal‐Saban et al , ; Rosenblum ; Zwicker et al ; Lingam et al ). Adolescents and young adults with DCD were also reported to have difficulties with concentration and memory, abstract subjects such as mathematics, the use and manipulation of technical and technological equipment and physical demands (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties with communication were also reported, mostly with written and non‐verbal communication (Kirby et al . , , , ; Missiuna et al ; Kirby ; Tal‐Saban et al ; Rosenblum ; Zwicker et al ; Lingam et al ). Difficulties with written communication were related mostly to poorer handwriting skills of adolescents and young adults living with DCD compared with their peers (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation